(untitled) (Dhaka University Journal of Science, 2022)
In this study, an Econometric analysis has been conducted to identify the important factors that affect the food grain productions in Bangladesh. Here, we have considered time series data for the years from 1989- 1990 to 2019-2020. Vector Autoregressive (VAR) Model and Autoregressive Integrated Moving Average (ARIMA) model have been considered in this study. Both these models have been considered to forecast the productions of food grains in Bangladesh. The forecasting performances of these two models have been compared by using RMSE, MAE, and MAPE. It has been found that the VAR model is better than the ARIMA model to forecast the food grain production. On the other hand, it has been come out from the analysis that there is no significant impact of chemical fertilizer on the food grain production, but irrigation area has significant impact on the food grain production. Among the three variables: food grain production, irrigation area and chemical fertilizer, there exists short run relationship. Dhaka Univ. J. Sci. 70(1): 8-13, 2022 (January)